Sexing the Citizen : Morality and Masculinity in France, 1870-1920 - Surkis, Judith (Book collections on Project MUSE., 2006)
This cultural and intellectual history provides new insights into how concerns about sexuality shaped the Third Republic's pedagogical projects. Surkis's analyses of republican moral philosophy and Emile Durkheim's sociology illustrate the cultural weight of these concerns and provide an account of modern French thinking about society. More broadly, Sexing the Citizen illuminates how sexual norms continue to shape the meaning of citizenship"--Jacket